2018
DOI: 10.14429/djlit.38.2.12298
|View full text |Cite
|
Sign up to set email alerts
|

Research on Plagiarism in India during 2002-2016 : A Bibliometric Analysis

Abstract: The issues of plagiarism have been mushrooming more rapidly around the globe. India is also not spared from plagiarism and related issues. Various researchers and academicians have raised their concern on rapidly growing cases of plagiarism. In this study, an analysis was made to identify the average growth of publications written on plagiarism by Indian authors, the degree of author collaboration, most impactful sources for publishing on plagiarism. The data for the period of 2002 -2016 were extracted from Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…The most common reason was, unsurprisingly, plagiarism (which includes self-plagiarism). Surprisingly, the number of retraction notices for Indian authors due to plagiarism was lower than that in Chauhan's (2018) research on plagiarism by Indian authors. He found that there were 385 articles in the SCOPUS database during the period 2002-2016.…”
Section: Reasons For Retractioncontrasting
confidence: 68%
“…The most common reason was, unsurprisingly, plagiarism (which includes self-plagiarism). Surprisingly, the number of retraction notices for Indian authors due to plagiarism was lower than that in Chauhan's (2018) research on plagiarism by Indian authors. He found that there were 385 articles in the SCOPUS database during the period 2002-2016.…”
Section: Reasons For Retractioncontrasting
confidence: 68%
“…ese shi s have brought about a highly diversi ed sta and student body and assumptions about shared literacy practices have been challenged (Angélil-Carter, 2000). Alongside these pressures has emerged a growing concern with incidents of plagiarism (Chauhan, 2018). While plagiarism is indeed a real problem that threatens the credibility of our universities and the knowledge produced within them (Kharat, Chavan, Jadhav, & Rakibe, 2013), there are concerns that our conception of plagiarism is o en un-theorised and not particularly helpful (Elander, 2015).…”
Section: Introductionmentioning
confidence: 99%